6u-6=-9(u-1)

Simple and best practice solution for 6u-6=-9(u-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6u-6=-9(u-1) equation:


Simplifying
6u + -6 = -9(u + -1)

Reorder the terms:
-6 + 6u = -9(u + -1)

Reorder the terms:
-6 + 6u = -9(-1 + u)
-6 + 6u = (-1 * -9 + u * -9)
-6 + 6u = (9 + -9u)

Solving
-6 + 6u = 9 + -9u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '9u' to each side of the equation.
-6 + 6u + 9u = 9 + -9u + 9u

Combine like terms: 6u + 9u = 15u
-6 + 15u = 9 + -9u + 9u

Combine like terms: -9u + 9u = 0
-6 + 15u = 9 + 0
-6 + 15u = 9

Add '6' to each side of the equation.
-6 + 6 + 15u = 9 + 6

Combine like terms: -6 + 6 = 0
0 + 15u = 9 + 6
15u = 9 + 6

Combine like terms: 9 + 6 = 15
15u = 15

Divide each side by '15'.
u = 1

Simplifying
u = 1

See similar equations:

| ifBC=RLthen | | 36+12m^2+m^4=0 | | 4a*3a= | | ln(6x+2)=ln(3x-19) | | -4.3-3z-2.9-z=-3z+5.7 | | -8m-8n+p-2=-10n-9p+8 | | 12*x^2-4=0 | | t(2t+-1)=1 | | 10-(4x-1)=8-5x | | 7x+21(2x-3)=180 | | 8c*3c= | | 3x+22x-4=5(5x+6) | | (-7b+4a)+(-6a-9b)= | | 5w^2+39w+5y=0 | | 9a+19=100 | | X^2-2x+528=0 | | 98=-2(-8x+8) | | 8cos^2x-4cosx-2=0 | | 6g=6g+-34 | | 3x+x+7=6x-2x+7 | | 0.25d+6=11 | | =5x | | N-3.5=6.5 | | 9f+15=15 | | (xy^2+y)dx+(x^2y-x)dy=0 | | 3+x/2=10 | | 8=4(b-2)+4 | | 32=-5x-8 | | 12(2p+11)=12(2p+12) | | 4x+12x-7=4(4x+9) | | -1=-2y+7 | | -15=9-8x |

Equations solver categories